PROFITABILITAS MEMODERASI FINANCIAL LEVERAGE DAN PERTUMBUHAN PERUSAHAAN TERHADAP PERATAAN LABA - Indawati Indawati; Anggun Anggraini (Universitas Pamulang, 2019)
The purpose of this study is to determine and analyze the effect of Profitability Moderating Financial Leverage and Company Growth partially and together on Income Smoothing. The research method used in this study is a quantitative method. Data taken is secondary data from manufacturing companies listed on the IDX. Based on the results of the study, the following findings are found: The Effect of Financial Leverage based on Return On Assets (ROA) on income smoothing from research results Provides information that Financial Leverage based on Return on Assets (ROA) has a positive and significant effect on income smoothing (ROA) Income Smoothing). The influence of company growth based on Return On Asset Equity (ROE) on income smoothing based on the results of research that has been done can be concluded that company growth has a significant and significant effect on income smoothing, so if there is an increase in company growth then income smoothing will increase. The Effect of Financial Leverage on Profitability Moderated Profit Flattening It can be concluded that Financial Leverage and Company Profitability moderated Growth simultaneously influence Profit Smoothing. The effect of company growth on profit smoothing moderated by profitability, it can be concluded that company growth has significant and significant effect on income smoothing with moderated profitability. Effect of Financial Leverage, company growth which is moderated by profitability to income smoothing, it can be concluded that Financial Leverage and Company Growth which is moderated by Profitability have a simultaneous effect on Income Smoothing. Keywords: profitability, financial leverage, income smoothing.